An optimal voltage synthesis technique for a power-efficient satellite application - Kang, Dong-In; Suh, Jinwoo; Crago, Stephen P. (Annual ACM IEEE Design Automation Conference: Proceedings of the 39th conference on Design automation : New Orleans, Louisiana, USA; 10-14 June 2002, 2002)
This paper presents an optimal voltage synthesis technique for a satellite application to maximize system performance subject to energy budget. A period of a satellite's orbit is partitioned into several independent regions with different characteristics such as type of computation, importance, performance requirements, and energy consumptions. Given a periodic energy recharge model, optimal voltages for the regions are synthesized such that the overall performance is maximized within the energy budget in the period.